Relationships between agricultural energy and farming indicators - Martinho, Vítor (2021)
Cutting costs in farms is the main concern for several stakeholders, specifically for farmers. Reducing energy costs allows for, at the very least, two relevant outcomes, one concerning increases in the net farm income and the other relating to the environment and the promotion of more sustainable farming and rural development. In turn, the agricultural sector may itself be a relevant source of renewable and clean energies. Considering these motivations, this research/study has intended to explore the concept of agricultural energy, highlighting the main insights from literature, and to stress the relationships between this concept and relevant farming in- dicators. The findings obtained may provide interesting support for the several related stakeholders, namely, policymakers, farmers and researchers. To achieve these objectives, literature available on scientific platforms was explored and statistical relationships were established, through econometric approaches (allowing for spatial effects), between structural characteristics from farms in the European Union. The findings reveal that the several instruments within the Common Agricultural Policy (CAP) should further address the relationships between financial support and sustainability. For example, it could be interesting to index the direct payments from the 1st CAP Pillar with farm indicators that consider dimensions related with the efficiency and savings in costs. In the current context, it is possible to increase the output and area with energy cost growths of 0.423 and 0.375% points, respectively, and increase the total crops output/ha growth and the utilised agricultural area with energy costs/ha growth of 0.243 and 0.225% points, respectively.